An Environmental Information System for Tanjung Mulia Village, Medan Municipality, Indonesia - Arjuna, Jaya (1996)
The residential area in any municipality is an area that ideally should pay special attention to the development of environmental management and pollution control. Most households in developing countries are located close to industrial activities and this may cause environmental problems such as water and air pollution The government or the Local Authority may not be able to cope with this problem of pollution perhaps due to financial constraints and lack of technology and expertise. Moreover, law enforcement is mostly ineffective due to lack of knowledge on the part of officials involved in environmental management. The objective of the study is to develop an Environmental Information System on human activities, location and sources of pollution in urban residential areas because such a study has not been previously undertaken. Decision makers will therefore be provided with an important tool that will furnish them with complete and accurate information to help them plan and implement a programme for sustainable growth of the city. The Indonesian Government has laid a valuable and solid foundation for a environmental information system through a system of land codes for tax collection. The land in cities has been given location codes in relation to the width and type of building; and width of each land unit. The linkage and relation between the tax administrative system and environmental management system constitutes the basic structure in the formulation of the environmental information system developed in this study. The Environmental Information System study consists of data collection, processing and analysis of data and data presentation. Data collection and organisation were based on the Environmental Audit Guidelines declared by the Indonesian Ministry of Environment in 1994. The concept of unit operation in a factory is applied to each land unit in the study area. The system that was developed was implemented in the three Subvillages of Tanjung Mulia Village, Medan Municipality, Indonesia. The study covered 152 locations of land units. The parameters obtained in this study such as distribution of population and solid and liquid waste handling systems was analysed by a Geographic Information System (GIS) and the output is presented in thematic maps. This data may be useful for environmental management and pollution control and land development planning of the study area.